2018
DOI: 10.31174/send-hs2018-185vi31-17
|View full text |Cite
|
Sign up to set email alerts
|

Communication Peculiarities of International and Ukrainian Brands in Social Networks (Facebook, Twitter, Instagram)

Abstract: The main goal of the study is to find out the patterns and differences in the positioning of 10 international brands from the Forbes list and 10 leading Ukrainian brands in the most popular social networks. Through statistical and content analysis there have been identified the quantitative and qualitative indicators of their representation on Facebook, Twitter, Instagram, and also reviewed the frequency and thematic focus of publications. As a result, we have provided practical guidance on how to use social n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Besides, it is concluded that they did not make use of the advantages of social media platforms to build stronger dialogues with their stakeholders particularly during the pandemic days when most of their stakeholders were expected to stay home, work from home and also to search for new entrepreneurship, research and development opportunities which technoparks could offer. As for each principle of dialogic communication, it is clear that Instagram accounts were preferred mostly for disseminating information (as also found in the studies of Silkü-Bilgilier and Kocaömer in 2020, and Arslan in 2019), while Facebook accounts were used mostly for attracting audiences for their return visits (which results in deficiency in dialogic communication as discovered by Haro-de-Rosario, Sáez-Martín, & del Mar Gálvez-Rodríguez, 2017;Saxton & Waters, 2014;Capriotti & Losada-Díaz, 2018;Oltarzhevskyi et al, 2018;Shin et al, 2015 in their studies), and the technoparks mostly used features of Twitter that made it possible to keep audiences on the platform (which shows important similarities with the major findings of prior research such as Rybalko & Seltzer, Connectist: Istanbul University Journal of Communication Sciences, 2021, 60, 1-26 2010; Kemna, 2013;del Mar Gálvez-Rodríguez et al, 2016;Beverly, 2013;Shin et al, 2015;Yue et al, 2019). This may signal the different social media strategies of technoparks for each platform, which, if that is the case, demonstrates that there is no consistency among those strategies.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Besides, it is concluded that they did not make use of the advantages of social media platforms to build stronger dialogues with their stakeholders particularly during the pandemic days when most of their stakeholders were expected to stay home, work from home and also to search for new entrepreneurship, research and development opportunities which technoparks could offer. As for each principle of dialogic communication, it is clear that Instagram accounts were preferred mostly for disseminating information (as also found in the studies of Silkü-Bilgilier and Kocaömer in 2020, and Arslan in 2019), while Facebook accounts were used mostly for attracting audiences for their return visits (which results in deficiency in dialogic communication as discovered by Haro-de-Rosario, Sáez-Martín, & del Mar Gálvez-Rodríguez, 2017;Saxton & Waters, 2014;Capriotti & Losada-Díaz, 2018;Oltarzhevskyi et al, 2018;Shin et al, 2015 in their studies), and the technoparks mostly used features of Twitter that made it possible to keep audiences on the platform (which shows important similarities with the major findings of prior research such as Rybalko & Seltzer, Connectist: Istanbul University Journal of Communication Sciences, 2021, 60, 1-26 2010; Kemna, 2013;del Mar Gálvez-Rodríguez et al, 2016;Beverly, 2013;Shin et al, 2015;Yue et al, 2019). This may signal the different social media strategies of technoparks for each platform, which, if that is the case, demonstrates that there is no consistency among those strategies.…”
Section: Discussionmentioning
confidence: 88%
“…As one of the leading social networking platforms, Facebook offers its users to share information, create and sustain constant interaction (such as conversation, negotiation, discussion, exchange, and so on), and cultivate dynamic relationships with their key audiences, which in turn gives way to developing strong dialogue, through its powerful dialogic functions (Capriotti & Losada-Díaz, 2018) such as comments, reactions, polls, and events and the like. Unlike some prior research (Kim et al, 2014b), more recent studies (Haro-de-Rosario, Sáez-Martín, & del Mar Gálvez-Rodríguez, 2017;Saxton & Waters, 2014;Capriotti & Losada-Díaz, 2018;Oltarzhevskyi et al, 2018;Shin et al, 2015) assert that many organizations manage their Facebook accounts only for disseminating information instead of establishing a two-way dialogue.…”
Section: Technoparks As Dynamically Powerful Technology Development Zones (Sanayi Vementioning
confidence: 93%
See 1 more Smart Citation